The Cathexis Reflection of Ode on a Grecian Urn by John Keats in the Light of Sigmund Freud’s Theory of the Unconscious Mind - Çamur, Ayşe (Advances in Social Sciences Research Journal, 2022)
Ode on a Grecian Urn by John Keats delineates a theory of unconsciousness in the light of Sigmund Freud’s psychoanalytic perspective. This study scrutinizes Freud’s theory of the unconscious mind in the way which penetrates one of the most memorable and notable poems, Ode on a Grecian Urn by John Keats in the Romantic Period. It shall then carry on perusing Keats in a novel layer, adopting Sigmund Freud’s theory of the unconscious mind as a cathexis reflection of the poem. By juxtaposing the psychoanalysis perspective and the noteworthy poem, Ode on a Grecian Urn, the research unveils in what aspects Freud’s psychoanalytical interpretation conveys the psychological stimulus behind the poem. The research probes the extent that John Keats’s reflection on the poem plays a pivotal role as a cathexis in the sense of Freud’s theory of the unconscious mind, which is the area that the reader sees the concepts psychoanalytically articulating in the poem. From the late 18th to the mid-19th century, framing the Romantic Period, this study attempts to disclose the unconscious impulse behind Keats’s reflection on the poem by demonstrating how the poem decodes itself as a way of cathexis from Freud’s term of Sublimation.